2021
DOI: 10.3390/nu13010258
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IIb Randomized Controlled Trial Investigating the Effects of Tocotrienol-Rich Vitamin E on Diabetic Kidney Disease

Abstract: Diabetic kidney disease (DKD) is a debilitating complication of diabetes, which develops in 40% of the diabetic population and is responsible for up to 50% of end-stage renal disease (ESRD). Tocotrienols have shown to be a potent antioxidant, anti-inflammatory, and antifibrotic agent in animal and clinical studies. This study evaluated the effects of 400 mg tocotrienol-rich vitamin E supplementation daily on 59 DKD patients over a 12-month period. Patients with stage 3 chronic kidney disease (CKD) or positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 28 publications
0
40
0
1
Order By: Relevance
“…Although the role of vitamin E (a traditional antioxidant) for kidney diseases is unlikely to help much, 98 , 99 a recent phase IIb randomized controlled trial found that 400 mg tocotrienol-rich vitamin E supplementation for 12 months could ameliorate the progression of diabetic kidney disease (assessed by serum creatinine and eGFR). 100 Therefore, these results indicated that oxidative stress is a promising therapeutic target in the context of CKD.…”
Section: Therapeutic Approaches That Target Chronic Hypoxia In Ckdmentioning
confidence: 93%
“…Although the role of vitamin E (a traditional antioxidant) for kidney diseases is unlikely to help much, 98 , 99 a recent phase IIb randomized controlled trial found that 400 mg tocotrienol-rich vitamin E supplementation for 12 months could ameliorate the progression of diabetic kidney disease (assessed by serum creatinine and eGFR). 100 Therefore, these results indicated that oxidative stress is a promising therapeutic target in the context of CKD.…”
Section: Therapeutic Approaches That Target Chronic Hypoxia In Ckdmentioning
confidence: 93%
“…Additionally, a pilot randomized, double-blind, placebo-controlled trial investigated the effects of 400 mg of a TT-rich vitamin E product for 12 months on the renal function of the supplementation of patients with stage 3 chronic kidney disease (CKD). Vitamin E improved kidney function, as revealed by serum creatinine, as well as estimated glomerular filtration rate [ 185 ].…”
Section: Effects In Humans Regarding Cardio-metabolic Healthmentioning
confidence: 99%
“…The same is supported by available literature that ideal dose range should vary between 200-400mg. 11 The different finding was observed where duration of study was 24 weeks and 430mg olive oil extract as a source of totoctrienol was used and significant effects were observed to improve quality of life for diabetic patients [11,12].…”
Section: Diabetes Mellitus (Dmmentioning
confidence: 99%
“…Despite having similar structure and antioxidant properties, these isoforms differ in their bioavailability and metabolism [1]. The other difference is the amount of saturation tails whereas tocotrienols have unsaturated isoprenoid side chain with three double bonds [2].…”
Section: Introductionmentioning
confidence: 99%